PENGARUH DOSIS PUPUK NPK DAN ZEOLIT TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (ALLIUM ASCALONICUM L.) VARIETAS BIMA BREBES - Muaz, Fachri; Dukat, Dukat; Nur, Subandi (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2024)
This purpose of the experiment to investigate the effect of NPK Fertilizer and Zeolit on Growth and Yield Of Shallot (Allium ascalonicum L.) of Bima Brebes Cultivar.The experiment was conducted at Babakan Village, Pakusamben Sub- Distric Cirebon Regency, West Java. The location above 9 m at high of sea level, Latosol field, the type of rain includ the type of D rain (medium). The research was conducted on March until May 2017.The method used to experimental method using a factorial Randomized Block Design pattern, the treatment consists of two factors were repeated three times. The first factor was dosage of NPK fertilizer that consisted of three levels M1 (400 kg/ha), M2 (500 kg/ha) and M3 (600 kg/ha). While the second factor is dosage zeolit that consist of four levels Z0 (kontrol), Z1 (2 ton/ha), Z2 (4 ton/ha) and Z3 (6 ton/ha).The results showed there was interaction between dosage of NPK and zeolite on the plant height at 25 and 35 DAP (Days After Plant), number of tillers at 35 and 45 DAP, and dry weight of bulb per plot. The treatment of NPK 600 kg/ha (M3) fertilizer gave the best result on dry weight per plot which produces 3,51 kg/plot, or equivalent to 15,3 ton/ha or Z3 (zeolite 6 ton / ha) gave the best result on dry weight of bulbs per plot which produces 3.71 kg/plot or equivalent to 16,2 tons/ha. Plant of height at 24 and 45 DAP was positively corrected with dry weight of bulb per plot.